Efeito da adição de açúcares e do processo de envelhecimento na qualidade sensorial de amostras de cachaça obtidas tradicionalmente e por redestilação - Santos, Vitor Rocha dos [UNESP] (2015)
Due to the demands of the new cachaça consumer market, the producers started worrying about adding value to the drink, investing in new technologies, staff improvement, quality control and offering more sophisticated packaging. Practices like the sugar adding, redistillation and ageing have being used like standard ways and to improve the sensorial characteristics of the drink, aiming to decrease the strong taste of ethanol and potentially sensorial defects, targeting on the improvement of the quality in the final product. This study assessed the effect of the traditional refined sugar addition and of the liquid sugar in the sensorial quality of the cachaça, comparing traditional samples and redistilleted, aged or no. The analyzed samples were obtained from the same traditionally distillated and reditillated brandy lot, added of 0,5% of sugars (refined and liquid), subjected to triangular tests aiming at a comparative analysis between the effects of the use of sugars. The samples, traditional and redistillated were aged in oak barrels for three years. These processes originated the samples: 1 - Traditional with no addition of sugar, 2 - Traditional adding 5g/L of liquid sugar, 3 - Redistillated with no addition of sugar, 4 - Redistillated adding 5g/L of liquid sugar, 5 - Traditional without sugar aged for 1 year, 6 - Redistillated without sugar aged for 1 year, 7 - Traditional without sugar aged for 3 years and 8 - Redistillated without sugar aged for 3 years. These samples were sensorially assessed by acceptance test, according to these parameters: color, flavour, taste, sweet taste and global impression, in addition to the purchasing behavior. The volatiles' profile of the traditional and redistillated samples was determined too, aiming to compare the samples taken from the redistillation process. The levels of copper and ethyl carbamate from the traditional ...